Omega-3 in the Prevention of Cardiovascular Diseases - Cerón Sandoval, Martha Izbeth; Sandoval Gallegos, Eli Mireya (Mexican Journal of Medical Research ICSA, 2017)
In the last years, Mexico has experimented changes in the epidemiological and nutritional transition. There is a decrease of communicable diseases and an increase of chronic diseases, becoming the main causes of death, mainly cardiovascular diseases. Experimental, epidemiological and interventional studies have demonstrated the beneficial cardiovascular effects of eicosapentaenoic acid (EPA) and docosahexanoic acid (DHA), which have antiatherosclerotic, antithrombotic, antiarrhythmic and anti-inflammatory effects. The American Dietetic Association recommend an ingestion of 250 to 1000 mg/day of omega 3. This paper mentions the functional characteristics, biosynthesis and mechanisms of omega-3 fatty acids. This paper also reviews the clinical evidence that support their role as a cardioprotective factor. Derived from the analysis of the reviewed studies, it is concluded that taking into account the benefits of omega-3 fatty acids in the prevention and treatment of cardiovascular diseases, it is necessary to increase the consumption of foods rich in these fatty acids.